An Empirical Analysis of Scientific Attitude among Undergraduate Students in Agricultural Sciences - Raghu Ananthula; Rajender Jatoth (Journal of Extension Education)
This study explored the determinants of scientific attitude among undergraduate agriculture students in Telangana State of India, analyzing their attitude levels and demographic influences. A sample of 250 B.Sc. Agriculture students from Professor Jayashankar Telangana Agricultural University was surveyed using random sampling. Factor analysis, normal probability curve, and inferential analysis revealed that most students exhibited a moderate scientific attitude, with significant differences based on gender, age, and parental occupation. Male students and those below 19 showed higher engagement, while students from government-employed families had the highest scores. Findings suggested the need for targeted educational strategies, including curiosity-driven learning, hands-on experiments, gender equity, early exposure, and infrastructure upgrades, to enhance scientific attitudes in agricultural education.